Resource Estimation Using Ordinary Kriging on Pit X, PT. Indo Muro Kencana, Tanah Siang District, Murung Raya Regency, Kaliamtan Tengah - Achmad Reza Kurniawan; Nur Ali Amri (ReTII, 2019)
The purpose of research is to analyze the grade distribution of gold epithermal vein low sulphidation resource based on geostatical ordinary kriging. The research area (Pit X) is located in Tanah Siang subdistrict, Murung Raya regency, Central Borneo. The research area belongs to mining owner company PT. Indo Muro Kencana. The data are 569 drillholes with drillhole spacing is 8 meters and sampling 1 meter per gold gold epithermal assay. Geostatistical methods consist of two methods, median indicator kriging and ordinary kriging. The parameters of grade estimation gold epithermal are based on variogram study and the result of crossvalidation of two geostatistical methods. The research is conducted by using Micromine 2018. Ordinary kriging based on block kriging methods while median indicator kriging with the median value for each vein is used for the estimation of gold epithermal resources. The result of the crossvalidation shown that median indicator kriging with coefficient of corelation (r) value 0.587 and root mean squared error (RMSE) value 0.097 is more accurate method than ordinary kriging with coefficient of correlation (r) value 0.103 and roor mean squared error (RMSE) value 0.857. The classification of gold ephitermal resources is based on value of avarage distance of samples by looking to its histogram. The results of gold epithermal resources based on its avarage distance of samples value of ordinary kriging methods has measured resource with 27607 tons and the avarage grades is 2.237 Au ppm, indicated resource with 5092 tons and the avarege grades is 3.376 Au ppm, and inferred resource with 40317 tons and the avarage grades is 1.8 Au ppm.